Psychological ways of preparing to start by athletes; pre-performance language routines - Kotek, J.; Maciuszek, J. (Studies in Sport Humanities, 2017)
Introduction Article investigates direct psychological preparation to start by analysing techniques used by athletes to indicate an optimal starting state. Main goal was to diff erentiate pre-performance routines from sport mantras, understood as repetitive use of language, and to answer the question if the mantras have diff erent eff ects on the process of preparation to start. The article is based on own research and literature. Subjects and procedure Research contains survey, covering the issue of mental techniques used by athletes before the start (146 respondents). 15 interviewees were chosen for semi-structured interviews about use of pre-performance mantras. Results and conclusions The outcome was the defi nition of sport mantra and description of variations of its use. Diff erences between this technique and other strategies of mental preparation to start were described. The results of the study address that and the characteristics of the mantas technique. It also provides clues for teaching pre-performance preparation.